ANALISIS BUTIR SOAL ULANGAN TENGAH SEMESTER PADA MATA PELAJARAN MATEMATIKA DI SMP NEGERI 2 PUNGGUR - Budi Santoso; Siti Annisah; Sri Wahyuni (LINEAR: Journal of Mathematics Education, 2021)
One of the efforts to see the achievement of learning objectives is by doing activitiesevaluation of learning outcomes using quality test instruments. This study aims to determinethe quality of odd mid-semester test items in mathematics for class VIII at SMPN 2The end of the 2020/2021 school year which was carried out during the covid-19 pandemic.This type of research is descriptive quantitative research. The subjects of this research are students class VIII at SMPN 2 Punggur for the 2020/2021 academic year. Data collection techniques using the method documentation. The data used are student answer sheets and questions on the test mid semester. The analysis was carried out in terms of content validity, reliability, discriminatory power, level of difficulty, and effectiveness of distractors with the help of Microsoft Excel program.The results of this study indicate that, 16 items have very high validity, 4 items have high validity, and has reliability in the high category, of 0.77. 1 item has a distinguishing powervery good, 10 items have good discriminating power, 8 items have quite good discriminating power, and 1Items have very poor discriminatory power. 15 items have a moderate level of difficulty, and 5Items have an easy level of difficulty. 12 items have very good distractor effectiveness, 6 the items have good distractor effectiveness, and 2 items have poor distractor effectiveness.Thus, there are 14 items of very good quality, 4 items of good quality, and 2 items ofquestions are of medium quality.